TOKSISITAS LIMBAH CAIR MINYAK KELAPA SAWIT DAN UJI SUB LETHAL TERHADAP IKAN NILA (Oreochromis sp.) - Syafriadiman ' (Berkala Perikanan Terubuk, 2010)
Research of Toxicity of industrial palm oil waste water and sub lethal testto Oreochromis sp. has been conducted on November 1st 2007 to March 1st 2008in Aquaculture Technology Laboratory, Fisheries and Marine Science FacultyUniversity of Riau. Objective of this research is to determine the concentration ofa test material or the level of an agent that produces a deleterious effect onOreochromis sp. during a short-time exposure under controlled condition. In thisstudy, static 96-h acute toxicity tests were carried out using Oreochromis sp. astest organisms. Probit analysis using the computer software EPA and graphicalmethod were used to caculate the 96-h LC50 depending on data suitability. Resultsof the 96-h LC50 and Biological Savety Level of the industrial palm oil wastewater were 126,06 ml/l and 1.26 ml/l respectively.